Nursing Assistants’ Perspectives on Their Job Characteristics, Workload, and Wage: A Case Study of a Private Hospital in Bangkok - Wattanatinnachot, Khemmanit (Journal of Human and Society, Sisaket Rajabhat University, 2022)
The objectives of this study were to 1) to study the rationales of female nursing assistants at a private hospital in Bangkok for choosing to work in low-paid nursing assistant jobs 2) to study their rationales for remaining in their current jobs for several years and 3) to find out their future plans in the next 5 years. This research adopted semi-structured interviews with 20 nursing assistants from the outpatient departments of the diabetes center and the medical check-up center. The research findings showed that a majority of nursing assistants chose to work in nursing assistant jobs mainly due to the financial constraints of their parents. Moreover, the institutional constraints from the Thai education system obstructed them to obtain bachelor’s degrees from public universities. As a result of these constraints, they ended up studying a six-month nursing assistant course which was low human capital investment. Additionally, a majority of nursing assistants remained in their current jobs mainly due to their financial constraints. Other rationales were overtime pay, job stability from annual salary increases, social satisfaction in the workplace, hospital fringe benefits and career development. Regarding their future plans in the next five years, some of the nursing assistants wanted to become licensed practical nurses while those with children wanted to move back to their hometowns to look after their children and parents and wanted to run small businesses such as a grocery shop and a restaurant.